Monetary and Fiscal Policy Interactions over the Cycle: Some Empirical Evidence - Anton Muscatelli; Patrizio Tirelli; Carmine Trecroci (Center for Economic Studies and ifo Institute (CESifo), 2002)
This paper estimates VAR models to examine the response of monetary and fiscal policy to macroeconomic targets, and the interdependence between the two policy instruments. The models are estimated for a number of G7 countries. Our findings show that, whilst monetary and fiscal policy are increasingly used as strategic complements, the responsiveness of fiscal policy to the business cycle has decreased since the 1980s. We also demonstrate that shifts in the strategic interdependence between fiscal and monetary policy can be captured using Bayesian VAR models.
Keywords: 330